Pembentukan Karakter Siswa SMA Amir Hamzah Medan Berlandaskan Pilar Akhlak Dalam Buku Karya Buya Hamka - Hasibuan, Marhan; Hidayat, Muhammad Arif (Al-Ulum: Jurnal Pendidikan Islam, 2024)
This research examines the characteristic values of Amir Hamzah Medan High School students in relation to the environment that has a negative impact on character values, which needs to be balanced with the learning process to form good moral character values. In the learning process morality needs to be formed by researchers who observe the characteristics of the surrounding environment, especially to recognise the nature of each student. This is done through observation, data analysis, and discussion. Buya Hamka's book explains that the values of moral quality today are very different from the past. Today, some young people pay little attention to moral character. Some parents ignore this because of the reduced moral quality in Islam. Therefore, some people today do not attach much importance to morality and consider their actions to be right. Based on this assumption, the researcher observed the environment and used observational information and sources such as Buya Hamka's book to interpret everything related to the characteristic values of moral education. The results of the research data show that the role of parents in educating their children about character values is very important. This means that parents need to better understand good and straight morals.